Preparation of Salganicoff’s platelet strip - ZHOU Xu-bin; SALGANICOFF L; SEVY R (Acta Pharmacologica Sinica; Vol 7, No 3 (May 1986): Acta Pharmacologica Sinica, 2016)
Salganicoff’s platelet strip, a new biological preparation, is used to observe the behavior of the platelet contractible protein with isometric tension. By centrifuge the platelets were deposited on a flat surface of a highly compliant nylon mesh. With heating the platelets were irreversibly activated by the thrombin generated in the residual plasma. The mesh was cut into strips, which were mounted for recording tension. It contracted in response to aggregating agents and relaxed to antagonists. It contracted like clot retraction. Being consisted of almost entirely platelets, it was more specific and the response showed a better reproducibility. It is a convenient tool for the study of physiological and biochemical studies of platelets and fibrinolytic agents.